Application of Taguchi method in the optimization of process variation for 32nm CMOS technology - Elgomati H.A.; Majlis B.Y.; Ahmad I.; Salehuddin F.; Hamid F.A.; Zaharim A.; Apte P.R. (2023)
In this paper, we investigate the effect of four process parameters namely HALO implantation, compensation implantations, SiO2 thickness and silicide annealing time on threshold voltage (VTH) in complementary metal oxide semiconductor (CMOS) technology. The setting of process parameters were determined by Taguchi method in experimental design. The influence of the main process parameters on threshold voltage were determined using analysis of variance (ANOVA). The fabrication processes of the transistor were performed by a simulator namely ATHENA. The electrical characterization of the device was done by the a simulator of ATLAS. These two simulators were combined with Taguchi method to aid in design and optimizing process parameters. The other two parameter used in this experiments were Source/Drain (S/D) implantation dose and, silicide annealing temperature Threshold voltage (Vth) results were used as the evaluation parameters. The results show that the VTH value of 0.10308V and -0.10319V for NMOS and PMOS respectively. As conclusion, by utilizing Taguchi Method shown that process parameters can adjust threshold voltage (VTH) to a stable value of 0.103V that is well within ITRS prediction for 32nm transistor.